Speech reading ability in class 3 students MI Nurul Ikhsan - Nurul Hasya (Mitra Palupi, 2023)
Background: Reading is one of the important aspects that must be mastered by students, speech is also an important aspect in this study because it is to train students' confidence from an early age. Purpose: This study aims to determine the ability to read speech in grade 3 students of MI Nurul Ikhsan. Design and methods: This research is using quantitative descriptive methods. Results: The results of this study indicate that students who get the very good category are 10.5% for those who get the good category are 24%. which is commonly obtained by students, namely in the less good category as much as 31%. From the results of the study, it can be concluded that the ability to read speech in grade 3 students can be said to be not good.